2017
DOI: 10.1038/s41598-017-15292-x
|View full text |Cite
|
Sign up to set email alerts
|

Ilex latifolia Thunb protects mice from HFD-induced body weight gain

Abstract: Kuding tea is implicated in alleviating metabolic disorders in traditional Chinese medicine. However, the role of Ilex latifolia Thunb (kuding tea), one of the large leaf kuding tea species, in the prevention of the development of obesity remains to be determined. We show here that 7-week-old male mice treated with an Ilex latifolia Thunb supplement for 14 weeks were resistant to HFD-induced body weight gain and hepatic steatosis, accompanied by improved insulin sensitivity. Ilex latifolia Thunb supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In accordance with these cell culture data, a five-week feeding study in female C57BL/6 mice fed either a standard chow, a high-fat diet or a high-fat diet supplemented with an I. kudingcha 0.05% ethanol extract revealed that KTE blocks high-fat diet-induced body weight gain without suppressing food intake or inhibiting lipid absorption [3]. Similarly, the antiobesity potential of an aqueous extract of I. latifolia was confirmed by Wu et al [44]. Male C57BL/6 mice received either a normal diet, a high-fat diet or a high-fat diet supplemented with 0.33% aqueous KTE for 14 weeks.…”
Section: Antiobesity Activitymentioning
confidence: 65%
See 3 more Smart Citations
“…In accordance with these cell culture data, a five-week feeding study in female C57BL/6 mice fed either a standard chow, a high-fat diet or a high-fat diet supplemented with an I. kudingcha 0.05% ethanol extract revealed that KTE blocks high-fat diet-induced body weight gain without suppressing food intake or inhibiting lipid absorption [3]. Similarly, the antiobesity potential of an aqueous extract of I. latifolia was confirmed by Wu et al [44]. Male C57BL/6 mice received either a normal diet, a high-fat diet or a high-fat diet supplemented with 0.33% aqueous KTE for 14 weeks.…”
Section: Antiobesity Activitymentioning
confidence: 65%
“…Mice fed the KTE-supplemented diets gained less body weight than mice without KTE [44]. In both studies, it was suggested that KTE supplementation counteracted a high-fat diet-induced increase in white and brown fat mass in mice [3,44]. Furthermore, KTE treatment improved glucose homeostasis in high-fat diet-fed mice and prevented lipid accumulation in the liver [3,44].…”
Section: Antiobesity Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, reports have shown that caffeinated beverages from the genus Ilex , including Yerba Mate and Kudingcha, can reduce body weight and have great potential to be developed into anti-obesity drugs [ 78 ]. I. latifolia (0.33% aqueous extract was added to the HFD) showed protective effects against HFD-induced body weight gain in mice, accompanied by decreased adipocyte lipid accumulation and suppressed expression of lipogenic genes in the liver [ 90 ]. Furthermore, adipocyte size, adipocyte differentiation, and fat accumulation were also suppressed in obese rats after treatment with I. paraguariensis aqueous solution [ 91 , 92 , 93 , 94 ].…”
Section: Health Benefitsmentioning
confidence: 99%